Pa'lopian: The Mastery of Tanjung Bira Seafarers in Navigating the Nusantara with Phinisi Vessels in Indonesia - Demmallino, Eymal Bahsar; Lampe, Munsi; Ismail, Ahmad (Journal of Cultural Analysis and Social Change, 2026)
The successful voyages of the phinisi Nusantara, from historical crossings to Singapore and Malaysia during the Nusantara Kingdoms to late 20th-century expeditions to Vancouver, Madagascar, Australia, and Japan, highlight the exceptional skills of Tanjung Bira seafarers. This study explores the mastery of these sailors, known as Pa'lopian, in navigating the phinisi vessels. Conducted in Bira Village, South Sulawesi, Indonesia the research employs a constructivist framework using case studies and phenomenological analysis, with data gathered through observation, interviews, and documentation. The findings reveal that the seafarers’ expertise lies in their ability to integrate knowledge of winds, currents, and waves for safe navigation. The study advocates for preserving this traditional maritime knowledge by establishing a Community University to support its transmission, especially in the context of maritime tourism. Integrating these indigenous practices into modern educational systems is crucial for their survival and relevance.